Development and characterization of areca fiber reinforced polymer composite. (2019) - Dinakaran, K.; Ramesh, H.; Joseph, A.D.; Murugan, R.; Jothi, S.
Abstract: Use of natural fiber as reinforcement is a burgeoning field of research because of the ease of procuring raw materials, bio-degradable and environment friendly nature along with mechanical properties of the resulting composites that are comparable to synthetic fiber-reinforced composites. Areca owing to these very reasons along with low cost, light-weight further advocated by its tensile strength has pervaded the field of composite manufacturing. Different natural fibers have been used by many researchers for the development of bio-composites, but areca leaf fibers as a feasible fiber has seldom been researched or spoken about. This research article sheds light on the development and study of mechanical behavior of a natural fiber reinforced epoxy composite of areca fiber with different configuration of areca fiber orientation.